Vaksin Kanker - Radji, Maksum (Majalah Ilmu Kefarmasian, 2009)
Cancer vaccines are medicines that work by stimulating or restoring the immune system’s ability to fight cancers and disease. There are two types of cancer vaccines, prophylactic cancer vaccines, which are intended to prevent cancer from developing in healthy people, and treatment cancer vaccines, which are intended to treat already existing cancers by strengthening the body’s natural defenses against cancer. This article discusses about cancer vaccines including the role of microbes that are respon-sible of human tumor, the mode of action of cancer vaccines and the efficacy of human papillomavirus (HPV) vaccines in preventing various benign and malignant condi-tions, including cervical cancers caused by HPV.